Transpancreatic mattress suture with Vicryl mesh around the stump decreases postoperative pancreatic fistula after distal pancreatectomy. (17th September 2019) - Yoshida, Yuta; Matsumoto, Ippei; Matsumoto, Masataka; Kawaguchi, Kohei; Murase, Takaaki; Kamei, Keiko; Satoi, Shumpei; Takebe, Atsushi; Nakai, Takuya; Takeyama, Yoshifumi
Abstract: Background: Postoperative pancreatic fistula (POPF) after distal pancreatectomy (DP) remains the most common surgical complication. We have developed a novel stump closure technique after DP using transpancreatic mattress suture with Vicryl mesh (TMV) and reported our initial findings. The purpose of this study is to evaluate the efficacy of TMV compared to the conventional handsewn stump closure technique (CHS). Methods: This retrospective single‐center study included 165 consecutive patients who underwent open DP from January 2010 to May 2018. Of these, 71 patients underwent DP using TMV after September 2014 and 94 patients underwent DP with CHS. The surgical outcomes were compared between the two groups. Results: Clinically relevant POPF rate in the TMV group was significantly lower than that in the CHS group (5.6% vs. 17.2%, P  = 0.027). Morbidity rate was higher in the CHS group than that in the TMV group (16.9% vs. 27.7%, P  = 0.104). In the multivariate analysis, absence of additional organ resection (OR 3.57; 95% CI 1.18–10.43; P  = 0.025) and TMV (OR 0.24; 95% CI 0.07–0.73; P  = 0.010) were identified as independent preventing factors for clinically relevant POPF. Conclusion: TMV can be an effective stump closure technique for preventing POPF after DP. Abstract : Highlight Postoperative pancreatic fistula remains the most common surgical complication after distal pancreatectomy. Yoshida and colleagues reported that their stump closure technique using transpancreatic mattress suture with Vicryl mesh significantly decreased fistula rates compared with the conventional method, and that it was an independent preventive factor for clinically relevant postoperative pancreatic fistula.